Plumbagin induces apoptosis characteristics in HepG2 cells - Thach, Bui Dinh; Long, Le Thanh; Quynh Chi, Ho Nguyen; Duy, Nguyen Khac; Chung, Doan Chinh; Si, Do Minh; Ho, Nguyen Huu; Suong, Ngo Ke; Son, Hoang Nghia (Academia Journal of Biology, 2014)
This study is to investigate the relationship between anti-proliferative activity of plumbagin and apoptosis induction of plumbagin on HepG2 cancer cells. The results showed that plumbagin treated HepG2 cell density was decreased. The apoptotic morphologies were also observed in HepG2 cells after plumbagin treatment. Nucleus staining, RT-PCR and comet assay were applied to study apoptotic morphologies in HepG2 cells. Acridine Orange staining results demonstrated that fragmented HepG2 nucleus by plumbagin was one of the important proves for its apoptotic induced characteristics. Bax transcript expression was increased in plumbagin treated HepG2 cells. However, there was no difference of bcl-2 transcripts expression between plumbagin treated HepG2 and control, suggesting that plumbagin induced a change in bax and bcl-2 transcripts expression of HepG2. Comet assay was applied to measure genomic DNA fragmentation in HepG2 cells. Fragmented DNA percentage in comet tail and comet tail length were increased in HepG2 treating with higher plumbagin concentrations. In conclusion, plumbagin showed apoptotic induced activitiy through morphological changes in HepG2 cells.